Cheap, Tunable and Versatile Nanoparticles for Explosive Detection: Quantum Dots - Federica Mitri; Andrea De Iacovo; Serena De Santis; Lorenzo Colace (Proceedings)
In recent years, fluorescent probes based on quantum dots have become a popular tool for explosive detection. However, despite their high sensitivity, these probes still require lab-based instrumentation and procedures that are difficult to be converted into a small, low-power system. Furthermore, they are hardly applied to the detection of vapor-phase explosives, being limited to water samples. Herein, we propose two alternative ways of employing quantum dots as a sensing material to build simple devices for vapor explosive detection. First, we report on a compact optical system where a solid-state QD photoluminescent probe is successfully integrated with a QD photodetector on the same silicon chip. Therefore, a high-performance chemiresistive sensor whose electrical resistance changes proportionally to the target gas concentration is proposed.